Elements of Effective Teaching in Higher Education: Implication to Anatomy Education - Saiful Bahri, Talip; Zul Izhar, Mohd Ismail; Muhamad Saiful Bahri, Yusoff; Hermizi, Hapidin; Nor Farid, Mohd Noor; Siti Nurma Hanim, Hadie (Penerbit Universiti Sains Malaysia, 2022)
Teaching anatomy is a challenging task to anatomists as they need to stimulate students’ threedimensional visualisation ability. Despite the needs for lecturers to be competent in instructional design and delivery, many anatomists are unsure about elements of effective teaching as the fundamental work on this area is scarce. Since anatomy is mainly taught in the higher education institutions, it is pertinent to find a comprehensive definition and framework of effective teaching in universities that could be adapted into anatomy teaching. Hence, we performed a scoping review to unearth the features of effective teaching in higher education using the five-stage framework of Arksey and O’Malley, namely identification of research question, identification of relevant study, selection of suitable study, data charting, and result collating and reporting. Three databases (Google Scholar, Scopus and PubMed) were searched using two search terms with a Boolean combination: “effective teaching” and “higher education.” The initial pool of 1,708 topics was assessed for duplication, and study eligibility was evaluated using inclusion and exclusion criteria. Data were abstracted from 14 original articles by two independent researchers and a thematic analysis was performed. Findings revealed the following categories of effective teaching elements, which have been proven effective in the achievement of learning outcomes: (a) pragmatic teaching, (b) learning support, and (c) optimised classroom management. Each theme overlies several sub-themes that reflect substantial numbers of effective teaching elements. The review provides evidence that a teacher’s role is not limited to teaching but includes the provision of support to students and management of the classroom environment to optimise learning. This article previews the utilisation of these teaching elements in anatomy education and its implication to future medical education.